2013
DOI: 10.1021/ic401281x
|View full text |Cite
|
Sign up to set email alerts
|

Fate of a Giant {Mo72Fe30}-Type Polyoxometalate Cluster in an Aqueous Solution at Higher Temperature: Understanding Related Keplerate Chemistry, from Molecule to Material

Abstract: When the giant icosahedral {Mo72Fe30} cluster containing compound [Mo72Fe30O252(CH3COO)12{Mo2O7(H2O)}2{H2Mo2O8(H2O)}(H2O)91]·150H2O (1) is refluxed in water for 36 h, it results in the formation of nanoiron molybdate, Fe2(MoO4)3, in the form of a yellow precipitate; this simple approach not only generates nanoferric molybdate at a moderate temperature but also helps to understand the stability of {Mo72Fe30} in terms of the linker-pentagon complementary relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…4−17 The stability of this compound has extensively been studied in its solid state 18 as well as in its solution. 19,20 An amorphous form of this cluster-containing compound was recently reported by the pioneering group of Muller and co-workers. 21 The synthetic procedure 21 for this amorphous {Mo 72 Fe 30 } compound is quite comparable to that of ferrimolybdite, synthesized by Kerr et al, who also isolated a yellow amorphous substance in the course of synthesizing a yellow coating mineral (ferrimolybdite) frequently found on ores of molybdenum.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…4−17 The stability of this compound has extensively been studied in its solid state 18 as well as in its solution. 19,20 An amorphous form of this cluster-containing compound was recently reported by the pioneering group of Muller and co-workers. 21 The synthetic procedure 21 for this amorphous {Mo 72 Fe 30 } compound is quite comparable to that of ferrimolybdite, synthesized by Kerr et al, who also isolated a yellow amorphous substance in the course of synthesizing a yellow coating mineral (ferrimolybdite) frequently found on ores of molybdenum.…”
mentioning
confidence: 86%
“…When the same suspension is refluxed (100 °C) for 36 h, platelike morphology of nanoferric molybdate is obtained, as shown in Figure 3 (left), as was obtained from the crystalline {Mo 72 Fe 30 } compound. 20 We repeated this experiment of obtaining nanorosettes (at 70 °C) and nanoplates (at 100 °C) several times (section 9, Figures S19 and S20 in the SI). This transformation of a amorphous {Mo 72 Fe 30 } compound to a crystalline ferric molybdate does have a strong connection with Kerr et al's original work 1 describing the laboratory synthesis of a yellow coating mineral (ferrimolybdite), often found on molybdenum ores in nature.…”
mentioning
confidence: 99%
“…For experiments 1, 6, and 8 the Soxhlet purification process was conducted in air. The high temperature refluxing of EtOH in the presence of air, likely results in FeMoC degradation [33,34]. For experiment 5, FeMoC synthesis likely failed due to the unfavorable pH, which controls the relative formation of the Mo VI and Mo V centers.…”
Section: Optimization Of Femoc Synthesismentioning
confidence: 99%
“…The tungsten nanoblackberries compound {W 72 Fe 33 } NM has been formulated as Fe 3 [W 72 Fe 30 O 252 ­(CH 3 COO) 2 ­(OH) 25 ­(H 2 O) 103 ]·180H 2 O ( {W 72 Fe 33 } NM ), which unlike {Mo 72 Fe 30 } NM does not contain sodium ion but contains three extra ferric ions per {W 72 Fe 30 } cluster, as shown in Figure . The novelty of {W 72 Fe 33 } NM over {Mo 72 Fe 30 } NM is that the tungsten analogue is kinetically stable and does not disintegrate even at 200 °C to Fe 2 (WO 4 ) 3 , unlike {Mo 72 Fe 30 } NM , a kinetically labile substance, which on heating at 60–70 °C degrades to Fe 2 (MoO 4 ) 3 . , In this work, we report the synthesis and characterization of {W 72 Fe 33 } NM nanoblackberries. We also describe the electrocatalytic hydrogen evaluation reaction (HER) by water reduction catalyzed by {W 72 Fe 33 } NM and {Mo 72 Fe 30 } NM in a comparison mode with detailed kinetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that the tungsten nanoblackberries material is greatly superior to its molybdenum analogue {Mo 72 Fe 30 } NM as far as electrocatalytic water reduction performance and stability issues are concerned. We have given a rationale describing the driving force for the irreversible solid-state isolation of these nanoblackberries, which are known to be formed reversibly in dilute solution in the case of {Mo 72 Fe 17,28 In this work, we report the synthesis and characterization of {W 72 Fe 33 } NM nanoblackberries. We also describe the electrocatalytic hydrogen evaluation placed between the {Mo 72 Fe 30 } cluster units.…”
mentioning
confidence: 99%